Differential conditioning and long-term olfactory memory in individual Camponotus fellah ants - Josens, R. (2009)
Individual Camponotus fellah ants perceive and learn odours in a Y-maze in which one odour is paired with sugar (CS+) while a different odour (CS-) is paired with quinine (differential conditioning). We studied olfactory retention in C. fellah to determine whether olfactory learning leads to long-term memory retrievable 24h and 72 h after training. One and 3days after training, ants exhibited robust olfactory memory through a series of five successive retention tests in which they preferred the CS+ and stayed longer in the arm presenting it. In order to determine the nature of the associations memorized, we asked whether choices within the Y-maze were driven by excitatory memory based on choosing the CS+ and/or inhibitory memory based on avoiding the CS-. By confronting ants with a novel odour vs either the CS+ or the CS- we found that learning led to the formation of excitatory memory driving the choice of the CS+ but no inhibitory memory based on the CS- was apparent. Ants even preferred the CS- to the novel odour, thus suggesting that they used the CS- as a contextual cue in which the CS+ was embedded, or as a second-order cue predicting the CS+ and thus the sugar reward. Our results constitute the first controlled account of olfactory long-term memory in individual ants for which the nature of associations could be precisely characterized.